Designing A Dealer Service Management Information System Motorcycle with Unified Modeling Language (UML) Method - Mahardika, Fajar; Azizah, Nur (Ilmu Bersama Center, 2024)
Some motorbike service workshops generally do not use information technology, so there are several obstacles found in their business processes. Where the process of recording service data takes quite a long time because the data is still written manually using books, so there is still a lot of data that is still not neatly arranged. When inputting service data there are often errors, so that the service data is no longer accurate. Then checking, updating and searching for spare parts stock takes a long time, because there are no reports of spare parts stock that will run out or have already run out. So if there are consumers who need spare parts, it is often these consumers. The wait was quite long because the company checked manually by checking directly at the warehouse. The Unified Modeling Language design model can make it easier for system developers to design the system that will be created because of its object-oriented nature. This Motorcycle Dealer Service Management Information System can make it easier for workshop admins to process motorbike service data in Motorcycle Workshops. By using this Motorcycle Dealer Service Management Information System, you can save time and simplify admin performance in carrying out motorbike servicing and creating service transaction reports.